2011
DOI: 10.1182/blood-2011-04-351502
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of cladribine followed by rituximab in patients with hairy cell leukemia

Abstract: We conducted this study to determine the feasibility and safety of cladribine followed by rituximab in patients with hairy cell leukemia including the variant form (HCLv). Cladribine 5.6 mg/m 2 given IV over 2 hours daily for 5 days was followed ϳ 1 month later with rituximab 375 mg/m 2 IV weekly for 8 weeks.Responses were recorded and BM minimal residual disease (MRD) was evaluated after the completion of rituximab. Thirty-six patients have been treated in- IntroductionOver the past quarter century, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 31 publications
2
112
2
2
Order By: Relevance
“…The longest follow-up in our cohort (median 45 months for these patients) may explain this difference. However, even in case of combination with PA, relapse rate in our study (11 % after a median follow-up of 24.5 months) is still higher than published data, although to a lesser extent [15,16].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The longest follow-up in our cohort (median 45 months for these patients) may explain this difference. However, even in case of combination with PA, relapse rate in our study (11 % after a median follow-up of 24.5 months) is still higher than published data, although to a lesser extent [15,16].…”
Section: Discussioncontrasting
confidence: 82%
“…Whereas the largest series published to date concerns the use of rituximab in combination with PA for frontline therapy of HCL [14,15], this situation represents only 5 of the 49 treatments reported in our study, with an excellent treatment outcome (100 % CHR). Most of our patients were treated at relapse, after multiple courses of therapy and a median time of more than 6 years since HCL diagnosis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These researchers updated their experience in 45 HCL patients, 38 with untreated disease. 37 In 24% of patients, MRD was detected at the completion of cladribine and rituximab treatment. These studies demonstrate the effectiveness of rituximab in reducing or eradicating MRD.…”
Section: Sequential Therapymentioning
confidence: 99%
“…In contrast to the purine analogs, responses to Rituximab are achieved in 30 --50% of patients and less than 20% are CR. By contrast the combination of chemoimmunotherapy (Rituximab plus DCF or CDA) in patients who experience early relapse, multiple relapses or do not achieve a response to single agent purine analog demonstrates that this combination is highly effective [69,70]. Else et al reported the efficacy of a combination of DCF or CDA with Rituximab in eight multiple relapsed or refractory HCL patients with impressive results [69].…”
Section: Purine Analog Plus Antibody Therapymentioning
confidence: 99%